The Impact of Welfare Chauvinism on the Results of Right-Wing Populist Voting in Germany after the Refugee Crisis - Florian W. Bartholomae; Chang Woon Nam; Pierre Rafih (Center for Economic Studies and Ifo Institute (CESifo), 2020)
Based on an extended welfare chauvinism concept that more systematically integrates the labor market and public finance aspects, this paper examines the impact of the refugee crisis - which culminated in the EU in 2015/16 - on changes in voting behavior in Germany (revealed in the two German federal elections in 2013 and 2017), explaining the attitudinal preference for ethnic boundaries around national welfare systems and the emergence of the right-wing populist party AfD. For this dynamic approach, an OLS analysis is conducted based on county-level data. The variables are selected taking into account existing theoretical and empirical findings in the international context, combined with Germany-specific facts and experiences, local demographic and economic differences, and party-specific voter characteristics. Among the key empirical findings are sufficiently reliable indications of the occurrence of welfare-chauvinistic effects that led to the success of the AfD in the 2017 election.
Keywords: D72; F22; J15; P16; 330; welfare chauvinism; immigration; right-wing populist party; refugee crisis; German federal elections